THE INFLUENCE OF CALCIUM INTAKE TO POST MENOPAUSAL WOMEN MANDIBULAR BONE DENSITY - M. Lindawati S. Kusdhany; Irawati Ismail; Soenawan Soenawan (Faculty of Dentistry, Universitas Indonesia, 2015)
Some researchers stated that osteoporosis in other bones will also be accompanied by a decrease in mandibular bone density. SO tat several risk factors for osteoporosis in other bones will also become risk factors for mandibular bone osteoporosis. Calcium intake, body mass index, and estrogen levels were risk factors analyzed in this study. Mandibular bone density is important to maintain because of its relation with loss of teeth and success rate of prosthodontics treatment. The study design was unmatched case control.The subjects were taken from 226 postmenopausal women betwwn 50 - 75 years od age, who fulfill the inclusion criteria. One hundred and nine subjects with normal mandibular bone density categorized as cases and 117 subjects with mandibular bone osteoporosis categorized as controls. Mandibular bone density was analyzed using intra oral periapical radiographs. The resut of this study showed that calcium intake was the main protecting factors for mandibular bone osteoporosis (OR=3,789), followed by body mass index (OR=2,184), and estrogen level (OR=1,107).